2014
DOI: 10.1016/j.pbiomolbio.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific modeling of ventricular activation pattern using surface ECG-derived vectorcardiogram in bundle branch block

Abstract: Patient-specific computational models have promise to improve cardiac disease diagnosis and therapy planning. Here a new method is described to simulate left-bundle branch block (LBBB) and RV-paced ventricular activation patterns in three dimensions from non-invasive, routine clinical measurements. Activation patterns were estimated in three patients using vectorcardiograms (VCG) derived from standard 12-lead electrocardiograms (ECG). Parameters of a monodomain model of biventricular electrophysiology were opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 42 publications
(23 reference statements)
1
38
0
Order By: Relevance
“…Considering computational cost, most inverse problems in cardiac imaging consider simplifications in the forward model, as reviewed in the literature. () Recently, patient‐specific heart meshes and monodomain forward models have been studied with manual selection of optimal parameters . In addition, adjoint‐based PDE‐constrained optimization for the monodomain/bidomain models is developing,() but the number of large scale (3D) studies is still very limited with the notable exception …”
Section: Discussionmentioning
confidence: 99%
“…Considering computational cost, most inverse problems in cardiac imaging consider simplifications in the forward model, as reviewed in the literature. () Recently, patient‐specific heart meshes and monodomain forward models have been studied with manual selection of optimal parameters . In addition, adjoint‐based PDE‐constrained optimization for the monodomain/bidomain models is developing,() but the number of large scale (3D) studies is still very limited with the notable exception …”
Section: Discussionmentioning
confidence: 99%
“…The simulations were solved using the Continuity software platform (UCSD NBCR, La Jolla, CA, USA) with a double‐precision solver on a Linux‐based GPU cluster using a time step of 0.1 milliseconds to solve the partial differential equation and 0.01 milliseconds to solve ordinary differential equations of the cellular ionic model. The electrophysiology model solutions consisted of the time‐varying 3‐D distribution of voltage in the ventricles from which the vectorcardiogram (VCG) was computed . The simulated surface ECGs were derived from the VCG solutions using previously validated transformations and resulting simulated electrogram amplitudes for individual cycles were measured (including minor fluctuations if they represented a maximum or minimum voltage for a cycle).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Gregory et al [30] proposed a technique for MRI synchronization in high-field MRI that may even deal with arrhythmic beats (premature ventricular Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/10/15 9:04 PM contraction), commonly found in patients with ischemic histories or during stress perfusions studies. The computational methods are found to be promising for cardiac diseases and therapy planning through VCG analysis [83,90]. Villongco et al [90] also showed that patient specific models of ventricular depolarization can be used for estimating the left-bundle branch block and right ventricular-paced activation sequences from VCG parameters for a single dominant excitation wave.…”
Section: Computational Methods For the Diagnosis Of Cardiac Diseasesmentioning
confidence: 99%
“…The computational methods are found to be promising for cardiac diseases and therapy planning through VCG analysis [83,90]. Villongco et al [90] also showed that patient specific models of ventricular depolarization can be used for estimating the left-bundle branch block and right ventricular-paced activation sequences from VCG parameters for a single dominant excitation wave. However, most cardiac diseases and activation sequences generally involve complex wave dynamics with multiple wavefronts, where the proposed single activation site and fixed dipole equivalent source model may be ineffective in describing the ventricular depolarization patterns in detail.…”
Section: Computational Methods For the Diagnosis Of Cardiac Diseasesmentioning
confidence: 99%